2022
DOI: 10.3389/fcimb.2022.821780
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Metabolome Changes in Mice With Acute Vestibular Deficit

Abstract: Vestibular deficit is a very common disorder in clinical practice and is characterized by vertigo, spontaneous nystagmus, and autonomic nervous symptoms, including nausea, vomiting, and sweating. In addition, the comorbidity of vestibular deficit and anxiety has long been an integral component of the medical literature. Previous studies have suggested that the mechanisms underlying this comorbidity involved overlap of vestibular and cerebellar networks. Emerging evidence has shown that the microbiota–gut–brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…To date, only one study has been conducted using a myopic animal model. 31 The results of this study showed that the relative abundance of Firmicutes decreased while that of Actinobacteria increased significantly in myopic mice.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…To date, only one study has been conducted using a myopic animal model. 31 The results of this study showed that the relative abundance of Firmicutes decreased while that of Actinobacteria increased significantly in myopic mice.…”
mentioning
confidence: 60%
“… 64 In the myopia-induced mice study, Bifidobacterium was found to be a dominant genus in myopic mice. 31 Li et al 31 also found that Bifidobacterium was positively correlated with axial length in the myopic mice. These findings suggest that the possibility of Bifidobacterium playing a role in the mechanism of myopia warrants further investigation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar change was obtained in the study of Zhang et al [ 40 ]. However, we observed an increased amount of Lachnospiraceae_NK4A136_group and Odoribacter in the ZW3 group, which were reported to produce short-chain fatty acids (SCFAs), such as propionic, acetic, and butyric acids [ 41 ]. In addition, ZW3 significantly reduced the abundance of the pathogen Escherichia-Shigella ( p < 0.05), which was positively correlated with colitis severity.…”
Section: Discussionmentioning
confidence: 99%
“…As with Lactobacillus , Muribaculaceae also produce short-chain fatty acids that exert anti-inflammatory and neurotransmitter-regulating effects ( Smith et al., 2019 ). Lachnospiraceae NK4A136 has been associated with vestibular disorders and neuropathic pain combined with anxiety ( Li et al., 2022 ; Shen et al., 2022 ). Furthermore, in a mouse model of colitis, the abundance of the Lachnospiraceae NK4A136 was increased, suggesting that Lachnospiraceae NK4A136 may be associated with anxiety and inflammation( Shao et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%